Urban particulate matter increases human airway epithelial cell IL-1β secretion following scratch wounding and H1N1 influenza A exposure in vitro. (1st August 2015) - Hirota, Jeremy A.; Marchant, David J.; Singhera, Gurpreet K.; Moheimani, Fatemeh; Dorscheid, Delbert R.; Carlsten, Christopher; Sin, Don; Knight, Darryl
ABSTRACT Purpose: The airway epithelium represents the first line of defense against inhaled environmental insults including air pollution, allergens, and viruses. Epidemiological and experimental evidence has suggested a link between air pollution exposure and the symptoms associated with respiratory viral infections. We hypothesized that multiple insults integrated by the airway epithelium NLRP3 inflammasome would result in augmented IL-1β release and downstream cytokine production following respiratory virus exposure. Materials and Methods: We performed in vitro experiments with a human airway epithelial cell line (HBEC-6KT) that involved isolated or combination exposure to mechanical wounding, PM10, house dust mite, influenza A virus, and respiratory syncytial virus. We performed confocal microscopy to image the localization of PM10 within HBEC-6KT and ELISAs to measure soluble mediator production. Results: Airway epithelial cells secrete IL-1β in a time-dependent fashion that is associated with internalization of PM10 particles. PM10 exposure primes human airway epithelial cells to subsequent models of cell damage and influenza A virus exposure. Prior PM10 exposure had no effect on IL-1β responses to RSV exposure. Finally we demonstrate that PM10-priming of human airway epithelial cell IL-1β and GM-CSF responses to influenza A exposure are sensitive to NLRP3 inflammasome inhibition. Conclusions: Our results suggest the NLRP3 inflammasome may contribute to exaggerated immune responses to influenza A virus following periods of poor air quality. Intervention strategies targeting the NLRP3 inflammasome in at risk individuals may restrict poor air quality priming of mucosal immune responses that result from subsequent viral exposures.